Misconceptions, Misinformation and Politics of COVID-19 on Social Media: A Multi-Level Analysis in Ghana - Tabong, Philip Teg-Nefaah; Segtub, Martin (Frontiers in Communication, 2021)
Background: Ghana developed an Emergency Preparedness and Response Plan (EPRP) in response to the Severe Acute Respiratory Syndrome Coronavirus (SARS CoV-2) pandemic. A key strategy in the EPRP is to mobilize national resources and put in place strategies for improved risk and behavioural change communication. Nonetheless, concerns have been raised on social media about COVID-19 misinformation and misconceptions. This study used social media content to determine the types, forms and the effects of the myths, misconceptions and misinformation in Ghana’s COVID-19 containment. Method: The study was conducted in three phases involving the use of both primary and secondary data. Review of social media information on COVID-19 was done. This was complemented with document review and interviews with key stakeholders with expertise in the management of public health emergencies and mass communication experts (N=18). All interviews were transcribed verbatim and analyzed using NVivo 12. Results: The study showed a changing pattern in the misconceptions and misinformation about COVID-19. Initially myths were largely on causes and vulnerability. It was widely speculated that black people had some immunity against COVID-19. Also, the condition was perceived to cause severe disease among the elderly. These misconceptions served as risk attenuators among Ghanaians, especially the younger generation. As the infection evolved in the country, another misconception emerged that the hot climate in Africa inhibited viral replication and transmission only to be followed by speculations and conjectures that COVID-19 was being used as a biological weapon to target developed economics. For the management of COVID-19, the use of local remedies such Neem tree (Azadirachta indica) and herbal preparation also emerged. Myths about the efficacy of locally manufactured gin (akpeteshie) and hydroxychloroquine as prophylaxis led to abuse of such substances. Interview segments revealed the use of myths to propagate political agenda in the country. Conclusion: The study concludes that COVID-19 misconceptions and misinformation are widespread and cover the course of the condition. These myths necessitate culturally sensitive health communication strategies that take into account local perceptions of COVID-19 in order to tackle the circulation of misconceived messages about the pandemic in Ghana.